The YAP/TAZ Signaling Pathway in the Tumor Microenvironment and Carcinogenesis: Current Knowledge and Therapeutic Promises (2022)
The yes-associated protein (YAP) and the transcriptional coactivator with PDZ-binding motif (TAZ) are transcriptional coactivators, members of the Hippo signaling pathway, which play a critical role in cell growth regulation, embryonic development, regeneration, proliferation, and cancer origin and progression. The mechanism involves the nuclear binding of the un-phosphorylated YAP/TAZ complex to release the transcriptional enhanced associate domain (TEAD) from its repressors. The active ternary complex is responsible for the aforementioned biological effects. Overexpression of YAP/TAZ has been reported in cancer stem cells and tumor resistance. The resistance involves chemotherapy, targeted therapy, and immunotherapy. This review provides an overview of YAP/TAZ pathways’ role in carcinogenesis and tumor microenvironment. Potential therapeutic alternatives are also discussed.